The Effect of Auditor's Competency, Accountability and Ethics on Audit Quality of Public Accountant Firms (KAP) at Makassar - Ummu Kalsum (FEB Universitas Sultan Ageng Tirtayasa, 2021)
This study aims to examine the effect of competence, accountability, and auditor ethics on audit quality. The data in this study were obtained from auditors of the Public Accounting Firms (KAP) in Makassar who were willing to become respondents. This study uses primary data by conducting direct research in the field by giving questionnaires / question sheets to 30 respondents. Data analysis method used to test the hypothesis in this study is multiple linear regression. This study indicates that competence (X1) accountability (X2) and auditor ethics (X3) auditors have a positive and significant effect on audit quality by auditors of Public Accountant Firms in Makassar. This means that the higher the auditor's ability to maintain the competence, accountability, and ethics of the auditor, the quality of audits conducted will increase.